An approach to pharmaceutical care in palliative care (Research, Society and Development, 2025)
Pharmaceutical care plays a fundamental role in improving the quality of life for patients with serious and incurable diseases, such as advanced-stage cancer, within palliative care settings. This literature review aimed to analyze the role of pharmacists in managing drug therapy, providing symptomatic relief, and supporting patients and families in the context of oncological palliative care. The research was conducted in the PubMed, Scopus, SciELO, and Google Scholar databases, considering Portuguese-language publications from the last ten years. Peer-reviewed articles, theses, and dissertations addressing pharmaceutical practice in palliative care were included. The analysis revealed that pharmacists significantly contribute to managing symptoms such as pain, nausea, and dyspnea, in addition to conducting medication reconciliation, deprescribing inappropriate drugs, and educating patients and caregivers. Integrated work within a multidisciplinary team proved essential for therapeutic optimization and patient safety. It is concluded that pharmaceutical care is indispensable for the effectiveness of palliative care, requiring continuous training and inclusion in public health policies.